Effect of controlled-release PeriochipTM on clinical and microbiological parameters in patients of chronic periodontitis - Komal Puri; Vidya Dodwad; Kishore Bhat; Nikhil Puri (Wolters Kluwer Medknow Publications, 2013)
Background: The aim of the present study was to evaluate and compare the clinical and microbiological effectiveness of Periochip TM as an adjunct to scaling and root planing (SRP) with SRP alone in patients with chronic periodontitis. Materials and Methods: This randomized, split mouth, 3-month clinical and microbiological trial included 30 sites in 15 patients aged 30-50 years diagnosed with chronic periodontitis. In each patient, two bilateral pockets probing 5-7 mm were randomly assigned to test and control groups. The test group received SRP plus Periochip TM , whereas the control group received SRP alone. Clinical indices and anaerobic culture analysis was done at baseline, 1 month, and 3 months interval. Total bacterial count and analysis of four major periodontopathogenic bacteria Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Aggregatibacter actinomycetemcomitans (Aa), and Fusobacterium nucleatum (Fn) was done. Results: Significant improvement was obtained in all clinical variables in the test group as compared to the control group over the study period. Total colony counts were significantly reduced in the test group as compared to control over the period of time. At baseline Aa was recovered from 4 test group sites and 5 control group sites, Pg from 15 test group and 14 control group sites, Pi from 5 test group and 2 control group sites, Fn from 7 test and 7 control group sites. At 3 months, Aa was recovered from 1 test group and 4 control group sites, Pg from 4 test group and 8 control group sites, Pi from 1 test group and 1 control group site, Fn from 3 test and 4 control group sites. Conclusion: Periochip TM placement as an adjunct to SRP, showed promising results, when compared to SRP alone. Healthy microflora can be maintained for a longer period of time and delay in the repopulation by periodontopathic microorganisms was observed.